Diffusion tensor imaging of the rotator cuff muscles : optimisation of b value and number of diffusion direction for imaging at 3 Tesla MRI - Kamarudin, Mohd Nazlin (2018)
Background: Diffusion tensor imaging is a standard method for evaluation of musculoskeletal pathology. The objective of this study is to determine the optimal b-value and number of diffusion direction for diffusion tensor imaging of rotator cuff muscles in healthy subjects on 3.0 Tesla MRI. Methodology: 38 healthy volunteers were included in this prospective study. Diffusion tensor imaging (DTI) of the rotator cuff muscles (subscapularis, supraspinatus and infraspinatus muscles) was performed with single-shot spin-echo echo-planar imaging sequences in 16 and 32 diffusion directions. Three different b-values were selected for each diffusion direction: b-value 400 s/mm2, 600s/mm2 and 800s/mm2. Signal to noise ratio (SNR) was measured in each muscle at different b-values and number of diffusion direction, and average SNR were calculated. Statistical analysis was performed with one-way ANOVA and paired t-test. Mean and standard deviation were obtained for each DTI parameters, and level of significance was determined (p < 0.05). Results: The signal to noise ratio was highest for all three muscles at b-value 400s/mm2 (subscapularis, 40.255; supraspinatus, 38.203; and infraspinatus, 48.232) followed by b-value 600s/mm2 and 800s/mm2. The use of 32 number of diffusion directions had shown to improve SNR value compared to 16 diffusion directions (P<0.05). Conclusions: The optimal combination of b value and number of diffusion directions in DTI of rotator cuff muscles on 3.0 Tesla MRI is 400s/mm2 and 32 directions respectively.